Benthic species patterns in and around the Cape Canyon: A large submarine canyon off the western passive margin of South Africa - Filander, Zoleka; Smith, Adam N. H.; Cawthra, Hayley C.; Lamont, Tarron (Frontiers in Marine Science, 2022)
Although submarine canyons are internationally recognized as sensitive ecosystems and reported to be biological hotspots, regional studies are required to validate this consensus. To this end, hydrographic and benthic biodiversity data were collected during three cruises (2016-2017) to provide insights on the benthic patterns within South African canyon and non-canyon offshore areas. A total of 25 stations, sampled at 200-1000 m depth range, form the basis of the multivariate analysis. Diversity gradients were calculated and then differences were compared across substrate types and depth zones represented within 12 canyon and 13 non-canyon stations. Significant differences in both substrate and depth were evident, despite measures being highly variable. This observation of varying diversity in different substrates is in line with previous studies. No clear pattern was observed for species diversity (delta+). However, non-canyon stations overall showed a higher diversity in comparison to canyon stations. A notable peak in diversity is observed in canyon areas in the 401-500 m depth zone. Species richness followed an opposing pattern, as it decreased with depth and was consistently higher in canyon areas. These results align with the well-defined influence of depth-related variables on the distribution of taxonomic groups and the substrate available, at various scales. The eutrophic characteristic of the Benguela region may have attributed to the insignificant diversity differences between canyon and non-canyon stations. To assess the benthic species structure in canyon and non-canyon areas, we converted the 108 benthic species into a gamma+ matrix. We then modelled the biological assemblage response to predictor variables (substrate and depth). Although the canyon and non-canyon areas have an overlapping species composition, the main effects (canyon vs non-canyon, depth, and substrate) showed significant differences. Thirteen species were characteristic of canyon areas, whilst only three distinguished non-canyon areas. The region has a long history of anthropogenic activities, so the observed benthic assemblages may already be altered. The current study therefore provides the first detailed taxonomic description and analysis of benthic species profiles in the Cape Canyon and advances important baseline information necessary for understanding the ecological importance of the Cape Canyon.